Peningkatan Kemampuan Kognitif melalui Bermain Playdough - Susilowati, Endang (Indonesian Journal of Islamic Early Childhood Education, 2017)
This study aims to determine the effectiveness of playdough media to improve childrens cognitive abilities. The design of this study used classroom action research. The results show that for the "very good developing" category, from pre cycle as much as 6 children or 33,33%, in cycle I still 6 children or 33,33%, and become 10 child or 55,56%. For the "developing as expected" category, from 2 children or 11,11% in cycle I become 5 child or 27,78% and in cycle II become 8 child or 44,44%. For the "developing" category, in pre cycle of 2 children or 11.11% and then decreased to 1 child or 5.56% and in cycle II no children who entered the category began to grow or 0%. In the "under developed" category in the pre cycle of 8 or 44.44%, then in the first cycle is reduced to 6 children or 33.33% and in cycle II there is no children in âunder developedâ category, or 0%. It can be concluded that playdough media can improve childrens cognitive ability.